An atypical presentation of Kikuchi‐Fujimoto disease: A case report & literature review - Halawa, Abdul Rahman R. (Clin Case Rep, 2020)
The authors urge clinicians to consider the possibility of Kikuchi‐Fujimoto Disease associated with autoimmune hemolytic anemia with possible correlation with systemic lupus erythematosus in patients presented with lymphadenopathy and fever.